Globalization in prehistory contact, exchange, and the "people without history" - Boivin, Nicole 1970-; Frachetti, Michael D. (Cambridge University Press, 2018)
"Globalization in Prehistory challenges traditional historical and archaeological discourse about the drivers of social and cultural connectivity in the ancient world. It presents archaeological case studies of emerging globalization from around the word, from the Mesolithic period, through the Bronze and Iron Ages, to more recent historical times. The volume focuses on those societies and communities that history has bypassed - nomads, pastoralists, fishers, foragers, pirates and traders, among others. It aims for a more complex understanding of the webs of connectivity that shaped communities living outside and beyond the urban, agrarian states that are the mainstay of books and courses on ancient civilizations and trade. Written by a team of international experts, the rich and variable case studies demonstrate the important role played by societies that were mobile and dispersed in the making of a more connected world long before the modern era"--Provided by publisher.